2015
DOI: 10.1038/srep17431
|View full text |Cite
|
Sign up to set email alerts
|

Resonances of nanoparticles with poor plasmonic metal tips

Abstract: The catalytic and optical properties of metal nanoparticles can be combined to create platforms for light-driven chemical energy storage and enhanced in-situ reaction monitoring. However, the heavily damped plasmon resonances of many catalytically active metals (e.g. Pt, Pd) prevent this dual functionality in pure nanostructures. The addition of catalytic metals at the surface of efficient plasmonic particles thus presents a unique opportunity if the resonances can be conserved after coating. Here, nanometer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Since many metal combinations do not, some plasmonic-catalytic bimetallic geometries result in a gradient-alloy structure, which can also be beneficial for enhancing the plasmonic fields. For example, electron energy loss spectroscopy maps of Au octopods with AuPd tips show spatially localized resonances around the tips [97]. Alternatively, one can sacrifice distinct faceting by conventional alloying techniques like thermal annealing [92,98], or new colloidal synthesis techniques like probe-based lithography [99].…”
Section: Alloysmentioning
confidence: 99%
“…Since many metal combinations do not, some plasmonic-catalytic bimetallic geometries result in a gradient-alloy structure, which can also be beneficial for enhancing the plasmonic fields. For example, electron energy loss spectroscopy maps of Au octopods with AuPd tips show spatially localized resonances around the tips [97]. Alternatively, one can sacrifice distinct faceting by conventional alloying techniques like thermal annealing [92,98], or new colloidal synthesis techniques like probe-based lithography [99].…”
Section: Alloysmentioning
confidence: 99%
“…The era of the application of EELS for plasmonics has changed since 2007, when Nelayah et al [140] and Bosman et al [141] reported, almost simultaneously, first examples of spatial mapping the SPRs of individual nanoparticles at the nanometer scale by mono-chromated EELS in a STEM using the spectrum imaging (SI) technique developed by Jeanguillaume and Colliex in 1989 [142]. Ever since the above-mentioned precedent studies, EELS has been used to map plasmon resonances of different solid nanostructures including spherical nanoparticles, nanorods/nanowires, nanocubes, nanodisks, nanoprisms, nanostars, nanosquares, and nanodecahedra [31,50,[143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162]. Along with its capability to give information with high spatial and energy resolutions, EELS has the ability to reveal full modal spectrum including dark plasmon modes, which are invisible to optical spectroscopy techniques, in coupled nanostructures [31,145,148,152,155,163,164].…”
Section: Ultralocal Plasmonic Propertiesmentioning
confidence: 99%
“…Octopods of Au and Pd combine the catalytic and plasmonic of each element in a single nanostructure, prompted us to develop a facile one‐step and high‐yield synthesis for platinum tetrapods (Pt TPs) which may have enhanced catalytic properties than Pt NPs . Hollow carbon nanospheres (HCNSs), template from iron oxide nanoparticles using glucose as carbon source, are utilized to encapsulate the high‐performance Pt TPs to formulate the confined catalytic nanoreactors for hydrogenation of various nitro aromatic compounds and for electrochemical oxidation of hydrazine (Scheme ).…”
Section: Methodsmentioning
confidence: 99%